White Matter Development is Potentially Influenced in Adolescents with Vertically Transmitted HIV Infections: A Tract-Based Spatial Statistics Study - Li, J.; Wu, G.; Wen, Z.; Zhang, J.; Lei, H.; Gui, X.; Lin, F. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Convergent evidence indicates that HIV is associated with abnormal WM microstructure in adults. However, little is known about whether HIV affects WM development in adolescents. In this study, we used DTI to investigate the integrity of WM microstructure in adolescents with vertically transmitted HIV infections.MATERIALS AND METHODS: Fifteen HIV-positive adolescents with vertically transmitted infections and 26 HIV-negative controls participated in this study. Whole-brain analysis of fractional anisotropy was performed by Tract-Based Spatial Statistics to localize abnormal WM regions between groups. VOI analysis was further performed to explore the changes in diffusivity indices in the regions with fractional anisotropy alterations. Correlation analyses were used to assess the relationship between fractional anisotropy alterations and clinical measures within the HIV-positive group.RESULTS: Relative to HIV-negative controls, HIV-positive adolescents demonstrated significantly reduced fractional anisotropy in the corpus callosum, superior and posterior corona radiata, frontal and parietal WM, pre-/postcentral gyrus, and superior longitudinal fasciculus. In the affected regions, fractional anisotropy reductions were caused by an increase in radial diffusivity, and no changes were observed in axial diffusivity. Moreover, fractional anisotropy values in the bilateral frontal WM were negatively correlated with the duration of highly active antiretroviral therapy and were positively associated with the age at onset of highly active antiretroviral therapy.CONCLUSIONS: These findings suggest that early HIV infections may affect WM development, especially in the frontal WM, corpus callosum, and corona radiata in adolescents, which may be associated with hypomyelination and demyelination. Moreover, WM integrity may serve as a potential new treatment target.ADaxial diffusivityFAfractional anisotropyHAARThighly active antiretroviral therapyMDmean diffusivityRDradial diffusivityTBSSTract-Based Spatial Statistics